THE INFLUENCE OF LEARNING FACILITIES AND TEACHER COMPETENCE ON LEARNING INTERESTS OF STUDENTS AT SMK DIPONEGORO 1 JAKARTA IN THE PANDEMIC ERA - Jatiputri, Sekar Kinasih; Wolor, Christian Wiradendi; Sariwulan, Rd. Tuty (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to: 1) To find out the influence of learning facilities on the learning interest of students of SMK Diponegoro 1 Jakarta, 2) To find out the influence of teacher competence on the learning interest of students of SMK Diponegoro 1 Jakarta, 3) To find out the influence of learning facilities and teacher competence on the learning interest of students of SMK Diponegoro 1 Jakarta This research uses quantitative research methods with data analysis techniques in the form of multiple regression analysis with the help of SPSS software version 25. The sampling technique uses simple random sampling with a total sample of 152 students. This study used a survey method in the form of a questionnaire to see the competencies on students' learning interests. Based on the results of the analysis, it was found that learning facilities and teacher competencies together have a positive and significant effect on students' interest in learning.